Huma Betang Philosophy, Multicultural Life and Metaphysical Unification in the Upanisads - Puspo Renan Joyo (IAHN-TP Palangka Raya, 2023)
Advances in technology stimulate the migration of people from one region to another. This situation eventually faded the homogeneity in society. Heterogeneity as one of the characteristics of the new social order is not spared from being exposed to problems, which is the clash of civilizations. This article discussed Huma betang's philosophy on its relevance to multicultural life. This research is library research with a qualitative approach. The material objects of this research were the philosophy of huma betang, multiculturalism and metaphysical unification in the Upanishads. The data in this study were obtained through a review of documents that correlated with material objects. The data analysis used in this study includes interpretation, holistic and descriptive analysis. The results of the study showed that there is a harmony of views between the philosophy of huma betang, multiculturalism, and the Upanishads regarding the importance of fundamental values, which have an understanding and perspective that emphasizes interaction regarding the existence of every culture as an entity that has equal rights. The philosophy of huma betang, the unification of the Upanishad metaphysics, and multiculturalism have given rise to normative ideas about unity, harmony, tolerance, respect, appreciation, solidarity, equal rights of each culture and harmony.